Understanding Some Aspects of Discourse Acquisitionin NNs Setting - Tagor Pangaribuan (Bandar Lampung University (UBL), 2013)
What happens in EFL learners’ black box? This research is a quest for process-product in of learners’ classroom acquisition in non native setting (NNs). The question to quest is what discourse do these learners acquire? To what extent studentscontiniously improve when they learn english during the semester as shown in their writing. To what extent do the discourses are reflecting their English Communicative competence. The subjects covers learners of 2nd semester at English Department attending writing –I (2 credits). They have 16 sessions but the with diary as their extrawork activities to support their learnings. The interpretive analysis shows tentative trend that NNs learners, english communicative competence.Learningenglish in Nonnative (NNs) setting is tough matter. Thousands of english learners in Pematangsiantar Indonesia, and other places as well are striving to achieve more or less some good english. Every year these learners explore the routes, search what other says, and follow what teachers suggest. Every NNs learner hopes to get the right track. The following is a longitudional survey of how NNs english grow through semesters. The learners are 2nd semester students in writing I, backgriunded in rural or remote schools entering english department. They start with a strong motive to study english but with very limited prior knowledge after grade 12. The study focus on student’s writing.